(untitled) (Journal of Population and Development, 2021)
This study aims to analyze the determinants of maternal health care utilization in Nepal. Maternal health still remains a public health problem in Nepal though it has been improving in the last decade since the number of women seeking antenatal care and opting for institutional delivery has increased. This study is based on Nepal Demographic and Health Survey data of 2016. The sample size consists of 3998 married women aged 15-49 years who had a live birth in the five years preceding the survey. Bivariate analysis is used to examine the association between adequate ANC visits and institutional delivery. A strong association is observed between women’s higher level of education and women involved in non-agricultural occupation with receipt of antenatal care and choosing of institutional delivery. The study findings conclude that there is a significant gap among different sub-groups of women in Nepal in the utilization maternal health care based on factors like women’s age, place of residence, level of education, occupation and wealth status. In order to address the existing gap and variation in ANC service utilization, particular attention should be given to women from less education, poor wealth quintile, living in rural areas, utilization of services among older age group. The results of this study put forward the need for efforts from government bodies and agencies in implementation of appropriate policies and programs to bring an improvement in the use of maternal health care services in Nepal.